Infections after xenotransplantation. Issue 6 (December 2018) - Nellore, Anoma
Abstract : Purpose of review: Xenotransplantation offers a solution for the global shortage of available organs. However, cross-species transplantation and immunosuppression raises concerns about transmission of zoonotic infections to the recipient as well as to the public. Recent findings: Here, we review the major infections of concern after xenotransplantation, risks of their transmission, diagnostic, therapeutic as well as prevention modalities for these infections after xenotransplantation. This review is particularly timely in light of recent advances in porcine genome editing technology that allow removal of retroviral sequences. Summary: We cannot appreciate the full risk of infections after xenotransplantation in absence of clinical trials. However, there are guidelines for strict microbiologic monitoring and reporting, infectious diagnostic assay development, breeding and quarantine of graft source animals to limit infectious transmission.